2019
DOI: 10.1186/s12992-019-0465-y
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of health research capacity strengthening in low and middle-income countries: lessons for conflict-affected areas

Abstract: Conducting health research in conflict-affected areas and other complex environments is difficult, yet vital. However, the capacity to undertake such research is often limited and with little translation into practice, particularly in poorer countries. There is therefore a need to strengthen health research capacity in conflict-affected countries and regions.In this narrative review, we draw together evidence from low and middle-income countries to highlight challenges to research capacity strengthening in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
118
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(136 citation statements)
references
References 106 publications
3
118
0
Order By: Relevance
“…Therefore, there is limited understanding as to the extent to which researchers are engaged in KT or what types of supports or interventions encourage and enhance their KT practice. A LMIC-specific focus is warranted given the inherent challenges related to equity that LMIC researchers and research institutions face [25][26][27][28]. For instance, health research capacity in LMICs is insufficient [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there is limited understanding as to the extent to which researchers are engaged in KT or what types of supports or interventions encourage and enhance their KT practice. A LMIC-specific focus is warranted given the inherent challenges related to equity that LMIC researchers and research institutions face [25][26][27][28]. For instance, health research capacity in LMICs is insufficient [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…A LMIC-specific focus is warranted given the inherent challenges related to equity that LMIC researchers and research institutions face [25][26][27][28]. For instance, health research capacity in LMICs is insufficient [25][26][27]. In addition, research in LMIC regions is largely funded by donors from high-income countries (HICs) and, typically, a requirement for accessing the funding is the formation of partnerships between LMIC and HIC researchers, which are led by the HIC researchers [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, research findings without distributing and disseminating are death 26 . Conducting research in low-and middle-income countries (LMICs) often very difficult because of funding, structural capacity, "flexibility, persistence, cultural humility, patience, and passion 11 " for the study 27,28 . Research funding allocated in LMICs were only 10% whereas these countries disease burden were 80-90% 29-.…”
mentioning
confidence: 99%
“…Subsequently, publishing research findings from LMICs extremely difficult 1 . Nevertheless, the proficiency to carry out a research study and interpret research outcome were found frequently very inadequate, predominantly in resource-limited countries 27 . Additionally, health research capability is universally accepted as an index development in LMICs and is an essential prerequisite for attaining the Millennium Development Goals [32][33][34] .…”
mentioning
confidence: 99%